Examining the policy mix for broadband deployment in Wales: The role of informal coordination in the last mile. (February 2020) - Henderson, Dylan; Roche, Neil
This paper examines the challenges of deploying broadband policies at the local level. It is a topic that has received significant attention in urban and rural areas, with uneven access to broadband identified as an important issue by policy makers and researchers alike. While the broadband and regional development literature has highlighted the complexity of regional deployment, with reference to geographical metaphors such as the last mile, it has tended to downplay the underlying policy processes as actors seek to manage the deployment process over time and space. Drawing on the concept of the policy mix, the paper examines how actors seek to manage complexity between policy objectives. It does so by drawing on an in-depth case-study of broadband policy in Wales – 2012 to 2017, and shows deployment to be a contested process in the last mile, characterised by interaction between policy objectives in a range of policy areas including planning and highways. It is argued that coordination of these tensions represents a complex socio-spatial process in which local actors (government, households, businesses and broadband providers) engage in a negotiated process to find place-based, bespoke solutions to deployment problems.